Fundamental Approaches to Software Engineering 21st International Conference, FASE 2018, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings - Russo, Alessandra; Schürr, Andy (Theoretical Computer Science and General Issues,, 2018)
This book is Open Access under a CC BY licence.